Implementation of Raw Material Control Management System in Food Factories - Irma Hakim; Asdi; Entar Sutisman; Muhammad Rizki; Pandu Adi Cakranegara (Institute of Computer Science (IOCS), 2022)
Raw material control is done to ensure that raw materials are available when needed and in compliance with expectations. An extremely significant issue with a company's production efficiency is overcoming raw material inventories. The corporation will be exposed to a significant cost risk if the amount of raw materials it owns exceeds the needs that are anticipated for the production process, including risks related to storage costs and material deterioration. The research goal is to develop a raw control management system based on the study problem by modifying the way raw materials are used in the warehouse using the FIFO (First in First Out) technique. The study's findings include a functional system analysis, which includes the ability to manage user data, raw material production order data, raw material management, and raw material purchasing management. System outputs include reports on production orders, raw materials, and financial data pertaining to raw material purchases. Five blackbox testing scenarios demonstrate that the system is reliable and operating as needed by users.